Visual and cognitive functioning among older adults with low vision before vision rehabilitation: A pilot study - Aubin, Gabrielle; Phillips, Natalie; Jaiswal, Atul; Johnson, Aaron Paul; Joubert, Sven; Bachir, Vanessa; Kehayia, Eva; Wittich, Walter (Frontiers in Psychology, 2023)
Introduction: The occurrence of age-related vision changes is inevitable. However, some of these changes can become pathological. Research indicates that vision and hearing loss is correlated with age-related cognitive decline, and with a higher risk of developing dementia due to Alzheimer’s disease. Low vision rehabilitation could possibly be a protective factor against cognitive decline, as it provides the clients with compensatory strategies to overcome their visual deficits. Objectives & hypothesis: The aim of this pilot study was to assess correlations between visual and cognitive functions in older adults referred for low vision rehabilitation. We hypothesized that more severe impairment of visual acuity and contrast sensitivity would be correlated with more advanced levels of cognitive impairment. The second objective was to examine which of these correlations would remain significant once established variables that influence cognition are statistically removed (e.g., age, education). Methods: Thirty-eight older adults (age range: 66 to 97 years old) with a visual impairment (acuity < 20/70) were recruited before the onset of their low vision rehabilitation. They underwent vision (reading acuity, reading speed, contrast sensitivity), hearing (audiogram, speech-in-noise perception) and cognitive (global cognition, memory, executive functions) testing, and demographic information was obtained. Results & discussion: Correlations among global cognition and visual aid use, memory and reading speed, memory and contrast sensitivity, memory, and visual aid use, and between executive functions and contrast sensitivity were significant. Correlations between contrast sensitivity and memory, as well as between global cognition and visual aid use remained significant after controlling for age and education. The present study is relevant to clinicians who are assessing the cognitive status of older adults, such as neuropsychologists, because it highlights the importance of considering low vision when administering neuropsychological tests, especially to persons who have not yet received rehabilitation for their visual impairment.